Fermentation of Peanut Milk by Lactobacillus Acidophilus SNP-2 for Production of Non-Dairy Probiotic Drink. - Giyarto, Giyarto (2011)
Production of fermented peanut milk drink by Lactobacillus acidophilus SNP2 using equipments that can be applied in small scale industry was investigated. Peanut milk was extracted using equipments that belong to small scale industry of tofu. Peanut milk inoculated with Lactobacillus acidophilus SNP2 was incubated at 37C for 18 h in incubator that made for small scale industry. After fermentation time, the product contained lactic acid bacteria 9.4 x 108 CFU/ml, with 0.32% titratable acidity and pH 3.86. Sensory evaluation revealed that the panelists prefer the taste of product with addition of 6-10% sugar to that of lower concentration of added sugar. The numbers of lactic acid bacteria showed no marked change in the fermented peanut milk drinks during storage at 4C for 28 days, and still sufficiently high to exert beneficial effects in the host. After storage for 28 days, fermented peanut milk drink contained lactic acid bacteria 6.9 x 108CFU/ml, 0.66 % titratable acid with the pH 3.5. Fermented peanut milk drink can be used as a probiotic carrier. Fermentation of peanut milk drink by Lactobacillus acidophilus SNP-2 for production of non-dairy probiotic drink can be applied to small scale industry.